Fatigue crack growth in 2017A-T4 alloy subjected to proportional bending with torsion - D. Rozumek; S. Faszynka (Fracture and Structural Integrity)
The paper presents the results of tests on the fatigue crack growth for a constant moment amplitude under combined bending with torsion in the aluminium alloy AW-2017A-T4. The tests were performed under different values of the load ratio R. Plane specimens with stress concentrators in form of the external one-sided sharp notch were tested. A non-uniform fatigue cracks growth on both lateral surfaces of specimens was observed during experimental tests. Fatigue cracks were developing in the specimens in two stages; quarter-elliptic edge cracks were observed at the beginning, then evolving into through cracks